(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article discusses the categories that connect syntactic units and their importance. The aim of the work is to study the national and cultural features of English phrases, to reveal their general and specific aspects, and thus to further develop the theory of private, comparative and universal phrases.